The evolution and driving mechanism of education inequality in China: From 2003 to 2020. - Yuanzhi Guo; Xuhong Li (PLoS ONE)
Although China's education development has made great progress, there are obvious regional differences in China's educational development. A systematic investigation of the regional inequality in China's educational development and its driving factors is of great significance for optimizing the allocation of educational resources and giving full play to the critical role of education in regional development. In addition, the research on the evolution and internal mechanism of educational development inequality in China can also provide experience and reference for the Global South. Therefore, we construct a comprehensive evaluation index system to measure the level of regional educational development, reveal the regional inequalities in China's educational development, and employ spatial econometric model to dissect the factors influencing the regional inequalities. The results show that China's educational development level continues to increasing from 2003 to 2020, but a significant decrease in its growth rate. In this process, regional differences in education inequality in China have gradually narrowed, which can be confirmed by changes in the Gini coefficient and Theil index. In terms of direct spillover effects, the per capita fiscal expenditure on education and urbanization rate have positive effects. In terms of indirect spillover effects, per capita GDP and per capita fiscal expenditure on education have negative effects, while population density and urbanization rate have positive effects. After replacing the weight matrix and removing the extreme values, the model also passes the robustness test. However, this mechanism is heterogeneous in different regions, therefore, we put forward the corresponding policies and measures according to the regional driving effects of influencing factors.